Chasing Ghosts: Race, Racism, and the Future of Microbiome Research - Travis J. De Wolfe (American Society for Microbiology, 2021)
In this article, we argue that a careful examination of human microbiome science’s relationship with race and racism is necessary to foster equitable social and ecological relations in the field. We point to the origins and evolution of the problematic use of race in microbiome literature by demonstrating the increased usage of race both explicitly and implicitly in and beyond the human microbiome sciences.